A method to establish an "immortalized F2" sporophyte population in the economic brown alga Undaria pinnatifida (Laminariales: Alariaceae). Issue 6 (27th October 2020) - Shan, Tifeng; Pang, Shaojun; Wang, Xuemei; Li, Jing; Li, Qianxi; Su, Li; Li, Xiaodong
Abstract : Studies of quantitative trait loci based on genetic linkage maps require the establishment of a mapping population. Permanent mapping populations are more ideal than temporary ones because they can be used repeatedly. However, there has been no reported permanent sporophyte population of economically important kelp species. Based on the characteristics of the kelp life cycle, we proposed a method to establish, and then constructed experimentally, an "immortalized F2 " (IF2 ) population of Undaria pinnatifida . Doubled‐haploid "female" and "male" sporophytes were obtained through the parthenogenesis of a female gametophyte clone and the selfing of a "monoicous" gametophyte clone (originally male), respectively, and they were used as the parents. The F1 hybrid line was generated by crossing the female and male gametophytes derived from the respective female and male parents. Full‐sibling F2 gametophyte clones, consisting of 260 females and 260 males, were established from an F1 hybrid sporophyte. Thirty‐five females and 35 males were randomly selected and paired to give rise to an IF2 population containing 35 crossing lines. A parentage analysis using 10 microsatellite markers confirmed the accuracy of the IF2 population and indicated the feasibility of this method. This proposed method may be adapted for use in other kelp species, and thus, it will be useful for genetic studies of kelp.